Il movimento invisibile del pensiero - De Simone, Gianfranco (Il sogno della farfalla, 2009)
The A. briefly analyzes the context in which M. Fagioli’s fundamental article Alcune note sulla percezione delirante paranoicale e schizofrenica (1962) was written and follows the subsequent development of the concepts introduced by it.